Predictors for de novo stress urinary incontinence following extensive pelvic reconstructive surgery - Tsia-Shu, Lp; Karim, Nazura; Nawawi, Erni Akhtar; Nusee, Zalina (Springer London, 2015)
Introduction and hypothesis The aim of this study was to lookfor possible predictors preoperatively for the development of de novo stress urinary incontinence (SUI) in urodynamically continent women who underwent pelvic reconstructive surgery(PRS). Materials and methods Medical records of 637 continent women who underwent PRS for severe prolapse from January 2005 to December 2013 in our institutions were includedin this study. We excluded women who had urodynamic stress incontinence (UDI) either occult or overt, detrusor overactivity, neurogenic bladder-voiding dysfunction,and previous anti-incontinent surgery. Primary outcome measure was the development of de novo SUI at 6 months to 1 year post operation. Results Of women in this study, 11 % developed postoperative de novo SUI at 6 months to 1 year of follow-up. Women older than 66 years were 2.86 times [95 % confidence interval(CI) 1.01–2.53, p=0.14], diabetes mellitus (DM) 2.18 times(95 % CI 1.63–4.21, p=0.002), certain type of transvaginal mesh procedure 3.5 times (95 % CI, p<0.001), maximum urethral closure pressure (MUCP)<60 mmH20 4.65 times (95 %CI, 2.87–8.64, p<0.001), and functional urethral length (FUL)<2 cm 3.48 times (95 % CI, 2.13–5.83, p<0.001) at greater risk of developing de novo SUI. Conclusions Continent women with advanced pelvic organ prolapse (POP)>66 years, with DM or low MUCP and FUL values during preoperative urodynamic evaluation have higher risk of developing de novo SUI; therefore, we suggest counselling such women for concomitant PRS and antiincontinent surgery.